Study on Genz’s Psychology and Brand Awareness Regarding Zudio Clothing Brand in Ahmedabad - Bansari Mansata; Chirag Chauhan; Jignesh Vidani (International Journal of Global Sustainable Research, 2024)
This study investigates the psychology of Generation Z (Gen Z) and their brand awareness of Zudio clothing in Ahmedabad. This research emphasizes the importance of a multi-channel marketing approach, blending traditional and digital strategies to engage a diverse consumer base effectively. Social media plays a crucial role, particularly in connecting with younger consumers, highlighting the need for Zudio to maintain a vibrant online presence. In recent years, the fascination of the fashion industry with sustainability and ecological challenges has grown significantly. The sustainable fashion sector offers immense potential, and the Ambiente program is luring eco-conscious shoppers from Generation Z with pragmatic products. Meanwhile, with remarkable consumption potentiality, Gen Z customers have captured the interest of researchers. Future research directions include longitudinal studies, comparative analyses across regions, and in-depth qualitative approaches to further explore the evolving dynamics of consumer-brand interactions. Overall, this study provides insights that can help brands navigate the complexities of engaging with Gen Z in a rapidly changing marketplace.